A model-based algorithm to correct for the loss of backscatter in superficial X-ray radiation therapy - Harwood, Jeffrey R.; Nelli, Flavio E. (Physica medica, 2019)
•Insufficient scattering material results in published Bw values that overestimate scatter.•An algorithm was developed for calculating backscatter in situations with reduced scattering medium.•Model validation by comparison with published data, Monte Carlo simulations and film measurements. Dosimetry protocols for superficial X-rays prescribe the determination of kerma on the surface of a phantom through the use of a backscatter factor (Bw) that accounts for the effect of phantom scatter. Bw values corresponding to full-scatter phantoms are provided by these protocols. In practice, clinical situations arise wherein there is insufficient scattering material downstream, resulting in published Bw values that overestimate the amount of occurring scatter. To provide an accurate dose calculation the backscatter values need to be corrected for any reduction in scattered radiation. Estimating the change of Bw in situations with incomplete backscatter has previously been achieved by direct measurements or Monte Carlo modelling. For increasing the accuracy of clinical dosimetries, we developed a physical model to deduce an algorithm for calculating backscatter factors in situations with reduced downstream scattering medium. The predictions of the model were validated by comparison with published data, Monte Carlo simulations and film-based measurements for beams with a half-value layer of 0.8, 2 and 4 mm Al. Our algorithm accurately predicts the effect of partial scatter conditions with suitable precision. Its reliability, combined with the simplicity of calculation, makes this methodology suitable to be incorporated into routine clinical dosimetry. The algorithm’s underlying physical model provides an intuitive understanding of the effects of field size and beam energy on backscatter reduction, permitting a rational management of this effect.